Peranan Kuliah Kerja Nyata (KKN) Sebagai Bagian Dari Pengembangan Kompetensi Mahasiswa di Desa Bintang Meriah - Madya, Efi Brata; Nabilah, Shofiyah; Bellasonya, Reza; Harahap, Siti Aisyah; Siregar, Arnisa Ramadhani; Nurhasanah, Sania (MODELING: Jurnal Program Studi PGMI, 2023)
Real Work Lecture (KKN) is an important component in higher education which aims to develop student competencies. KKN in Bintang Meriah Village is a program that provides opportunities for students to interact directly with the people in the village. This study aims to reveal the role of KKN as part of developing student competencies in Bintang Meriah Village. This study uses a qualitative approach with data collection techniques through interviews, observation, and document analysis. The results of the study show that KKN in Bintang Meriah Village makes a significant contribution to developing student competence. KKN gives students the opportunity to interact with various levels of society in Bintang Meriah Village. This helps students develop social competencies, such as the ability to communicate, work in teams, and understand cultural differences. Through direct experience in Bintang Meriah Village, students can understand in depth the social and environmental issues faced by the village community. This helps them become students who are more concerned about these problems. KKN provides valuable practical experience for students outside the academic environment. This can help them develop job skills relevant to their field of study. This study concludes that KKN in Bintang Meriah Village has an important role in developing student competence, both from a social, academic, and moral perspective. Therefore, KKN programs in villages should continue to be supported and improved so that students can make a greater positive contribution to society and develop themselves holistically.